Generalized diffusion theory of micromorphicly deformable particle-fluid continuum and bubble-liquid two-phase flows - Diep, Nguyen Van (Vietnam Journal of Mechanics, 1993)
In the paper [1] the basic concepts and equations were derived for the micromorphicly deformable particle-fluid two-phase flows, the constitutive equations have been constructed. The flow us fluid with deformable spherical particles, when the particle only expands radially, rotates and translates, is considered in this paper. For this case one can obtain the full motion’s equations system. These equation together with the constitutive equations are sufficient to determine all of unknowns, and they can be used to study the bubble- liquid two-phase flow. The problems of kinematic wave and acoustic wave propagation in the bubble-liquid two-phase flow is studied.